2019
DOI: 10.1108/cr-08-2018-0049
|View full text |Cite
|
Sign up to set email alerts
|

The impact of actors, networks and institutions in the cluster’s evolution

Abstract: Purpose This paper aims to analyze the impact of the capabilities and strategies of the actors (micro-dynamics), learning process and networks (meso-dynamics) and institutions (macro-dynamics) in the evolution of the Brazilian ceramic clusters. Based on these experiences, managerial and policy implications are suggested. Design/methodology/approach Main data were gathered through 22 in-depth face-to-face interviews with managers and industry experts. The data were complemented by documentary analysis, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…In a similar case, studies such as that of the ceramics industry in Brazil are observed, highlighting the dynamic capacities at different levels, such as the adaptation strategies that actors take at the micro dynamic level (companies), based learning processes in networks at the dynamic meso level (sector) and evolution by invoking institutions at the dynamic macro level (region) [38], capabilities that are also observed in other studies that analyze the impact on global business (GB) and entrepreneurship international (EI). In both cases, it can be ensured that adaptation, absorption and innovation capabilities co-create a business model in organizations, which is recognized by some authors, such as the vision of dynamic capabilities (VDC), In both cases, it can be ensured that adaptation, absorption and innovation capabilities co-create a business model in organizations, which is recognized by some authors, such as the vision of dynamic capabilities (VDC), model that It allows managing and shaping networks effectively, particularly in the face of turbulence in emerging markets [39].…”
Section: Relationships Between Dynamic Capabilities For Smes and Clusmentioning
confidence: 87%
“…In a similar case, studies such as that of the ceramics industry in Brazil are observed, highlighting the dynamic capacities at different levels, such as the adaptation strategies that actors take at the micro dynamic level (companies), based learning processes in networks at the dynamic meso level (sector) and evolution by invoking institutions at the dynamic macro level (region) [38], capabilities that are also observed in other studies that analyze the impact on global business (GB) and entrepreneurship international (EI). In both cases, it can be ensured that adaptation, absorption and innovation capabilities co-create a business model in organizations, which is recognized by some authors, such as the vision of dynamic capabilities (VDC), In both cases, it can be ensured that adaptation, absorption and innovation capabilities co-create a business model in organizations, which is recognized by some authors, such as the vision of dynamic capabilities (VDC), model that It allows managing and shaping networks effectively, particularly in the face of turbulence in emerging markets [39].…”
Section: Relationships Between Dynamic Capabilities For Smes and Clusmentioning
confidence: 87%
“…With a focus on the nondeterministic nature of regional evolution and existing external influence, the adaptive cycle perspective – was proposed by Martin and Sunley (2011). This idea of multiple regional path development and external influence has enrichened Cluster Life Cycle research and consequently was adopted in many studies (Carli and Morrison, 2018; Desmarchelier and Zhang, 2018; Mobedi and Tanyeri, 2019; Rodríguez-Rodríguez et al , 2016; Santner, 2018; Scur and Garcia, 2019). But it does not provide specific parameters by analyzing which would be possible to identify the stage of CLC.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Product life cycle theories (Levitt, 1965) and the industry life cycle (Klepper, 1997) serve as inspiration for the emergence of the CLC theory. The life cycles of clusters "and industries" are not the same; different clusters belonging to the same industry can follow different growth paths (Menzel and Fornahl, 2010;Scur and Garcia, 2019). Thus, clusters can grow or be diminished independently of industry development (Trippl et al, 2015).…”
Section: Cluster Dynamics (Clc)mentioning
confidence: 99%
“…women's hosiery). Scur and Garcia (2019) analysed the driving forces behind cluster evolution based on qualitative empirical research, with multiple case studies in Brazilian ceramic tile clusters. In the Crici uma cluster, which showed signs of being a declining cluster, firms improved their products and competed in a higher value market based on differentiation.…”
Section: Cluster Dynamics and Firms' Strategiesmentioning
confidence: 99%